She Came from Mariupol - Wodin, Natascha, 1945- (Book collections on Project MUSE., 2022)
"Natascha Wodin sets out on a quest to find out what happened to her mother, a forced laborer, from Mariupol, Ukraine, before and during the Second World War"--